2014
DOI: 10.3389/fnmol.2014.00070
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin-proteasome system in neurodegenerative diseases: precipitating factor, yet part of the solution

Abstract: The ubiquitin-proteasome system (UPS) has been implicated in neurodegenerative diseases based on the presence of deposits consisting of ubiquitylated proteins in affected neurons. It has been postulated that aggregation-prone proteins associated with these disorders, such as α-synuclein, β-amyloid peptide, and polyglutamine proteins, compromise UPS function, and delay the degradation of other proteasome substrates. Many of these substrates play important regulatory roles in signaling, cell cycle progression, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
208
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(216 citation statements)
references
References 188 publications
2
208
0
1
Order By: Relevance
“…Recent studies from our group and others demonstrated that disturbance of proteolytic machinery is a key feature of degenerating neurons and appears in several neurodegenerative disorders (4,8,15). Proteasome activity was found to be reduced in AD brains than in age-matched controls (38,50) and also in DS brain (17).…”
Section: Innovationmentioning
confidence: 81%
“…Recent studies from our group and others demonstrated that disturbance of proteolytic machinery is a key feature of degenerating neurons and appears in several neurodegenerative disorders (4,8,15). Proteasome activity was found to be reduced in AD brains than in age-matched controls (38,50) and also in DS brain (17).…”
Section: Innovationmentioning
confidence: 81%
“…Similar phenomena occur in mammalian models of disease when proteasomal function is inhibited or dysfunctional due to genetic alterations. Neurodegenerative diseases often display proteasomal defects due to accumulation of neurotoxic molecules such as alpha-synuclein, beta-amyloid or mutant huntingtin that can act as inhibitors of proteasome activity or by overwhelming proteasome activity [32]. Proteasomal involvement in regulation of mitochondrial function is also demonstrated by a number of proteasome components and ubiquitin E3 ligases that associate on the surface of the OMM, such IBRDC2, FBXW7, FBXO7, RFN185 in humans and Rsp5 and Dma1 in budding yeast (see references in [33].…”
Section: Links Between Protein Turnover and Mitochondrial Functionmentioning
confidence: 99%
“…Ubiquitin is added post-transcriptionally to flag proteins for degradation by the ubitiquitin-proteaseome system (UPS), and its elevation in CSF may reflect the gradual accumulation of unwanted proteins, perhaps including mHTT, in cells of the CNS. Failure of the UPS to cope with the buildup of abnormal proteins is suggested to be involved in the pathogenesis of HD and other neurodegenerative diseases [82]. This finding warrants further investigation and its longitudinal predictive value needs to be determined in a suitable patient cohort.…”
Section: Proteomic Approachesmentioning
confidence: 98%